Anomalous diffusion of water molecules at grain boundaries in ice Ih. Issue 20 (10th May 2018) - Moreira, Pedro Augusto Franco Pinheiro; Veiga, Roberto Gomes de Aguiar; Ribeiro, Ingrid de Almeida; Freitas, Rodrigo; Helfferich, Julian; de Koning, Maurice
Abstract : First-principles and classical molecular dynamics simulations show that diffusion of water molecules at pre-melted grain boundaries in ice is glassy-like, showing sub-diffusive behavior. Abstract : Using ab initio and classical molecular dynamics simulations, we study pre-melting phenomena in pristine coincident-site-lattice grain boundaries (GBs) in proton-disordered hexagonal ice Ih at temperatures just below the melting point T m . Concerning pre-melt-layer thicknesses, the results are consistent with the available experimental estimates for low-disorder impurity-free GBs. With regard to molecular mobility, the simulations provide a key new insight: the translational motion of the water molecules is found to be subdiffusive for time scales from ∼10 ns up to at least 0.1 μs. Moreover, the fact that the anomalous diffusion occurs even at temperatures just below T m where the bulk supercooled liquid still diffuses normally suggests that it is related to the confinement of the GB pre-melt layers by the surrounding crystalline environment. Furthermore, we show that this behavior can be characterized by continuous-time random walk models in which the waiting-time distributions decay according to power-laws that are very similar to those describing dynamics in glass-forming systems.